Los clústeres como alternativa estratégica para la competitividad de las pymes: Caso industria cuero y calzado en Perú; Clusters as a strategic alternative for the competitiveness of SMEs: case of the Leather and Footwear industry in Peru - Luis Alberto Benites Gutiérrez; Alexis Matheu Pérez; Rafael Espinoza Mosqueda; Claudio Ruff Escobar; Martin Inca Alayo; Marcelo Ruiz Toledo; Roberto Cortés Cancino (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2023)
– An Industrial Cluster constitutes a strategic unit to develop industrial policies to improve sustainable competitiveness, especially for small and medium-sized enterprises (SMEs). The objective of the research was to carry out the diagnosis of the supply chain in the tannery cluster, leather, and footwear the province of Trujillo (Peru), considering its strategy around 14 themes for analysis. The method used was the "Case Study", with a sample of ten SMEs from the most representative manufacturing sector. At the same time, the data processing was analyzed through Pearson's correlations and Kendall's correlation coefficient. The result of the analysis shows that the organizational variables with the greatest impact on the profitability of the Cluster is the capacity for innovation and an entrepreneurial culture. Likewise, considering the fundamental factors that favor the development of the leather-footwear Cluster, they are quality and trust for the exchange of information and the viability of constituting the Cluster, according to the affirmation of the respondents, who are Managers of 8 producing companies, 1 design producer and only one company as a supplier of inputs. In third place, the results of the multivariate statistical analysis show that, in regardto the development of the business Cluster model in leather-footwear, it is necessary to encourage the cooperation between the Institutions and finances, the confidence of the workers in the production processes and the technological resources with the administrative processes and of operations.
Keywords: L67; C02; 330; cluster leather footwear; manufacturing SMEs; multivariate statistical analysis